The Role of Purchase Intention in Mediating the Effect of Customer Review, Influencer Marketing, and Brand Awareness on Purchase Decisions - Ede Ramadhin Setyawanatra; Hadiah Fitriyah; Sriyono Sriyono (Dinasti International Journal of Education Management And Social Science, 2025)
Social media marketing strategies, customer reviews, and influencer marketing have influenced consumer behavior in purchasing products, particularly in the case of MS Glow cosmetic products, which experienced a decline in sales due to issues regarding the safety of the products. The purpose of this study is to investigate the influence of customer reviews, influencer marketing, and brand awareness on increasing consumer purchase intention, which can then affect the purchase decision on MS Glow cosmetic products. This research employed a quantitative research technique based on positivist ideology using multiple linear regression methods, where the object of the research is the official Shopee MS Glow Indonesia online store, with a population comprising all customers who have purchased MS Glow items through the internet, and a sample size of 100 people calculated using the Lemeshow formula, with primary data sources collected through the distribution of Google Form questionnaires. The research results show that customer reviews, influencer marketing, and brand awareness have a significant influence on purchase decisions, both directly and through purchase intention as a mediating variable. Customer reviews show a positive influence on purchase intention and purchase decisions, although there are indications of an unusual relationship that requires further investigation. Influencer marketing has been proven to have a strong positive impact on purchase intention and purchase decisions, while brand awareness also shows a significant positive influence on purchase intention and purchase decisions. Analysis of indirect effects through purchase intention shows a positive and significant effect of customer reviews, influencer marketing, and brand awareness on purchase decisions, emphasizing the importance of an integrated marketing strategy that considers all these aspects to increase purchase intention and ultimately drive purchase decisions.